1992
DOI: 10.1104/pp.100.3.1464
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Evidence for Osmoregulation of the Δ1-Pyrroline-5-Carboxylate Reductase (proC) Gene in Pea (Pisum sativum L.)

Abstract: Several cDNA clones encoding A1-pyrroline-5-carboxylate reductase (P5CR, L-proline:NAD[P]+ 5-oxidoreductase, EC 1.5.1.2), which catalyzes the terminal step in proline biosynthesis, were isolated from a pea leaf library screened with a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 35 publications
1
28
0
1
Order By: Relevance
“…Genes for the last enzyme of Pro biosynthesis, P5C reductase, were cloned from soybean, Arabidopsis, and pea (Delauney and Verma, 1990;Williamson and Slocum, 1992;Verbruggen et al, 1993), and it was observed that osmotic stress resulted in a similar increase in the P5C reductase message level as were seen for the P5CS message. The observation that salinity or dehydration stress stimulated the accumulation of the transcripts for the Pro-biosynthetic genes has been interpreted to mean that the transcriptional control of these genes is important for the regulation of Pro synthesis by osmotic stress.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Genes for the last enzyme of Pro biosynthesis, P5C reductase, were cloned from soybean, Arabidopsis, and pea (Delauney and Verma, 1990;Williamson and Slocum, 1992;Verbruggen et al, 1993), and it was observed that osmotic stress resulted in a similar increase in the P5C reductase message level as were seen for the P5CS message. The observation that salinity or dehydration stress stimulated the accumulation of the transcripts for the Pro-biosynthetic genes has been interpreted to mean that the transcriptional control of these genes is important for the regulation of Pro synthesis by osmotic stress.…”
mentioning
confidence: 99%
“…Arabidopsis, pea, and rice, which have been used to probe the importance of transcriptional control for Pro synthesis, are in fact not the best representatives of Pro accumulators. These plants accumulate only approximately 2 to 6 mol Pro/g fresh weight in response to NaCl stress (Williamson and Slocum, 1992;Savouré et al, 1995;Peng et al, 1996;Igarashi et al, 1997). Thus, unless it is highly concentrated in specific subcellular compartments or organelles, Pro at such low overall concentrations would not be expected to be a substantial determinant of the osmotic potential of the whole cells (Blum et al, 1996;Sharp et al, 1996).…”
mentioning
confidence: 99%
“…The expression of reductase (P5CR) is regulated by osmotic potential variation in the cytoplasm (Williamson & Slocum, 1992). An osmotic potential decrease induces the P5C biosynthesis, which results in proline synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, Anabaena 7120 has the GXXXA motif starting G235 onward representing the site for NAD(P) attachment. In line with pea, this domain also contains a GTTIAG sequence involved in NAD(P)H-ribose binding indicating that P5CR utilizes NAD(P)H as the co-factor (Williamson and Slocum 1992).…”
Section: Discussionmentioning
confidence: 99%